Qualidade fisiológica de semente de soja em função do tamanho da semente e da cultivar - Vendrame, Ronaldo João (2012)
This study aimed to evaluate the relationship among seed size and their physical and physiological attributes in three soybean cultivars (NK 7059 RR, SYN 3358 RR and BMX POTÊNCIA RR). Samples were collected from the Seed Processing Unit C.Vale in Abelardo Luz-SC, and the following analyzes were performed: seed germination , seed vigor, mechanical damage, screen retention and weight of 1000 seeds. The analyzes were performed at the Laboratory of Seeds Analysis C.Vale- Cooperativa Agroindustrial in Palotina-PR, and the following cultivars and screens were used: NK 7059 RR (5.75 and 6.75 mm), SYN 3358 RR (5.5 and 6.5mm) and BMX POTÊNCIA RR (5.75 and 6.75mm). The analysis of seed germination was performed according to the Brazilian Rules for Seed Analysis; the seed vigor test was based on the accelerated aging and the test with sodium hypochlorite was used for the evaluation of mechanical damage. Two replicates of 100 seeds were used for the screen retention test, which was determined by retention in specified screen and in screen without perforations. The weight of 1000 seeds was measured in eight replications of 100 seeds. The following conclusions were obtained: 1-Physiological seed quality is independent of seed size 2-There is higher seed retention on the superior screen, reaching more than 10%, and 3-Large seeds tend to have higher mechanical damage.